2023
DOI: 10.15557/jou.2023.0037
|View full text |Cite
|
Sign up to set email alerts
|

Role of high-resolution ultrasound and magnetic resonance neurography in the evaluation of peripheral nerves in the upper extremity

Ali Serhal,
Steven Kyungho Lee,
Julia Michalek
et al.

Abstract: Upper extremity entrapment neuropathies are common conditions in which peripheral nerves are prone to injury at specific anatomical locations, particularly superficial regions or within fibro-osseous tunnels, resulting in pain and potential disability. Although neuropathy is primarily diagnosed clinically by physical examination and electrophysiology, imaging evaluation with ultrasound and magnetic resonance neurogra- phy are valuable complementary non-invasive and accurate tools for evaluation and can help de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…In one study, it was observed that these symptoms could persist for up to 3 years postpartum. 13 This may be attributed to the frequent active use of the wrist during breastfeeding, potentially contributing to edema and inflammation. Another study investigating possible risk factors found that symptoms starting before the third trimester, an increase in the severity of CTS symptoms during pregnancy, and ongoing CTS postpartum were identified as risks.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was observed that these symptoms could persist for up to 3 years postpartum. 13 This may be attributed to the frequent active use of the wrist during breastfeeding, potentially contributing to edema and inflammation. Another study investigating possible risk factors found that symptoms starting before the third trimester, an increase in the severity of CTS symptoms during pregnancy, and ongoing CTS postpartum were identified as risks.…”
Section: Discussionmentioning
confidence: 99%